ANALISIS TINGKAT KECERAHAN WARNA IKAN PLATY PEDANG (Xiphophorus helleri) MELALUI PENAMBAHAN ASTAXANTHIN DENGAN DOSIS BERBEDA PADA PAKAN KOMERSIAL - Diana Rachmawati; Istiyanto Samidjan; Pinandoyo Pinandoyo (Fakultas Perikanan Universitas Pekalongan, 2017)
Platy sword fish (Xiphophorus helleri) is one of ornamental fishes which are commonly raised. The price of platy sword fish could decrease if they have fade coloration on their body. One of solution to improve and maintain quality of the color is by adding astaxanthine into its artificial feed. This study aims to analyze effects of the astaxanthine addition in artificial feed on an increase of color intensity of platy fish as well as to find optimal dose of astaxanthine. Fish used to be tested is platy sword fish ( X. helleri ) with the total of 120 tails in which they have an average weight of 2,0 ± 0,06 g per fish. Astaxanthine used in this study is obtained from PT. Indobeta Store Jakarta. While feed used in this study is commercial pellet containing protein 30 % and by adding astaxanthine based on the treatments, those are A treatment (0 mg astaxanthine/kgfeed), B treatment (100 mg astaxanthine/kg-feed), C treatment ( 200 mg astaxanthine/kg-feed ), and D treatment ( 300 mg astaxanthine/kg-feed ). Observation of the color intensity was conducted in 6 weeks using TCF (Toca Color Finder). The addition of astaxanthine into artificial feed with different doses can influence on the increase of color intensity of platy sword fish (X. helleri). Astaxanthine dose of 200 mg/kg feed is best dose for the increase of color intensity of platy sword fish (X heller ).Keywords: platy sword fish, astaxanthine, color intensity, survival rate